2019
DOI: 10.1039/c9ob01256g
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Amberlyst-15-catalyzed synthesis of complex hybrid heterocycles containing [1,6]-naphthyridine under metal-free green conditions

Abstract: Synthesis of complex hybrid heterocycles containing [1,6]-naphthyridine under metal-free green conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…They observed that the experimental rate constants were dependent on the percentage of urea in the carbohydrate melt; however, the best correlation was found to be with the solvent viscosity, which is in agreement with previous reports by the authors [67]. The Diels-Alder reaction of 9-anthracenemethanol (54) and N-ethylmaleimide (55a) in different solvent media under conventional heating and ultrasonic activation has been reported [68]. The influence of the solvent medium in the yield of the reaction was assessed by comparing DESs, obtained by the combination of different HBAs (e.g., choline chloride, methyltriphenylphosphonium chloride, (±)-menthol) and HBDs (e.g., glycerol (Gly), ethylene glycol (EG), urea), with water and organic solvents.…”
Section: Deep Eutectic Solventssupporting
confidence: 88%
See 4 more Smart Citations
“…They observed that the experimental rate constants were dependent on the percentage of urea in the carbohydrate melt; however, the best correlation was found to be with the solvent viscosity, which is in agreement with previous reports by the authors [67]. The Diels-Alder reaction of 9-anthracenemethanol (54) and N-ethylmaleimide (55a) in different solvent media under conventional heating and ultrasonic activation has been reported [68]. The influence of the solvent medium in the yield of the reaction was assessed by comparing DESs, obtained by the combination of different HBAs (e.g., choline chloride, methyltriphenylphosphonium chloride, (±)-menthol) and HBDs (e.g., glycerol (Gly), ethylene glycol (EG), urea), with water and organic solvents.…”
Section: Deep Eutectic Solventssupporting
confidence: 88%
“…The intramolecular Povarov reaction of 2-aminoarylaldehydes bearing a tethered alkyne moiety with heterocyclic amines catalyzed by Amberlyst-15 in PEG-200 has been described [54]. This metal-free green protocol allowed the synthesis of [1,6]naphthyridine-fused heterocycles 33 and 35 in good yields (60-81%) starting from 2-(N-Scheme 5.…”
Section: Polyethylene Glycolmentioning
confidence: 99%
See 3 more Smart Citations